Pendidik dan Insan Kamil dalam Perspektif Islam - Muttaqin, Khairul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Continuous discussion about the actors of education, namely humans in their roles as educators and students is very important. Understanding educators will provide guidance for educators in their efforts to carry out the education process for students. In relation to the role of educators in educating, realizing the best human being is the goal of education in Islam. The best human being in Sufism is known as the term insan kamil. This article tries to explain how Islamic teachings view educators and insan kamil. The study in this article is descriptive analytical, using a library research approach. From the results of the discussion, it was found that realizing humans in the form of insan kamil in the world of education will be difficult to achieve if not supported by the figure of an educator in the form of insan kamil. To get the figure of an educator in the form of insan kamil, it can be traced by knowing how the exemplary behavior of the Prophet Muhammad SAW and his companions in educating. Considering that the meaning of educator is very broad, encompassing all people or institutions who are dissatisfied with education, then efforts to realize perfect human beings are not only the task of Sufis, scholars, Islamic Religious Education teachers in schools, or Islamic Religious Education lecturers in universities, but the task of realizing human beings in the form of perfect human beings is a shared task and responsibility that involves all parties.